2013
DOI: 10.1111/ijn.12085
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric indicators of obesity as screening tools for high blood pressure in the elderly

Abstract: The study objectives were to investigate the indicators of obesity most associated with high blood pressure in community-dwelling elderly and identify among these which one best discriminates high blood pressure. This is an epidemiological, population, cross-sectional and home-based study of elderly people (≥ 60 years, n = 316) residing in northeastern Brazil. The results showed that the body mass index and the body adiposity index were the indicators more closely associated with high blood pressure in both se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
0
10
1
Order By: Relevance
“…Therefore these obesity indices show different screening powers for hypertension [ 11 16 ]. Gender differences in associations between obesity indices and hypertension were found by some studies [ 11 , 15 , 16 ], though the evidences were equivocal [ 12 14 ]. Some studies found the efficiencies of obesity indices for identifying hypertension decreasing with age [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore these obesity indices show different screening powers for hypertension [ 11 16 ]. Gender differences in associations between obesity indices and hypertension were found by some studies [ 11 , 15 , 16 ], though the evidences were equivocal [ 12 14 ]. Some studies found the efficiencies of obesity indices for identifying hypertension decreasing with age [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…23,22,50 These modifications increase the exposure to hypertension and cardiovascular disease, which can certainly be explained by the increased of the body fat mass. 50,22 Although not significant, there was a significant correlation from the clinical point of view between the number of diseases and BMI in men and women.…”
mentioning
confidence: 99%
“…19,20 Recent research have shown strong associations between overweight/ obesity and diabetes, 21 hypertension, 22,23 osteo-articular diseases 19 and disabilities. 21,24 On the other hand, low body weight is associated to chronic respiratory diseases and high mortality rate.…”
mentioning
confidence: 99%
See 2 more Smart Citations